Ways to improve efficiency of professional sports financing mechanisms - Litvishko, O. V.; Vysotskaya, T. P.; Bodrov, I. M.; Nosov, S. M.; Buyanova, V. T. (Theory and Practice of Physical Culture, 2019)
The national professional sports with their entertainment and commercial aspects cannot be competitive enough on the global arenas unless well supported by the governments and private interests in the current economic situation. The national sport industry strives to find efficient public-private-civil partnership formats for progress. Objective of the article was to take the global football industry for a case study to analyze benefits of the efficiency improvement projects in the national professional sports. Financial viability of the national sports system may be improved by the focused efforts to popularize healthy lifestyles, encourage the popular support for the national sports and spur up the private business interests in the sport industry. We analyzed the leading football clubs` financing systems in a few countries with a special attention to the match attendance statistics versus the football club profitability rates and proceeds from match broadcasting rights as visualized by a few diagrams in the study. It was concluded that the modern sport infrastructure and beneficiary sport teams shall be controlled by the same corporate entities to secure due synergy of the commercial supporters for progress of the sports.